National Park of Iti: Environmental and geomorphological impacts from the mining activity (Greece) - Mertzanis, A.; Karetsos, G.; Smyrni, V.; Efthimiou, G.; Zakinthinos, G. (Bulletin of the Geological Society of Greece, 2007)
Bauxite excavation and the inert material quarries, in the wider region of the "National Park of Iti" in combination with the forest fires, the illegal logging, the grazing and the uncontrollable waste disposal, constituted the most important pressures in it’s natural ecosystems. Particularly, bauxite ore exploitation that presented elation during the decade of ’70s, was implemented without planning and it caused alterations in the natural environment of the region mainly by the continuous excavations, the foreheads of galleries and the extensive depositions of aggregates materials. As a result, all the above led to the occupation or the deforestation of forests and woodlands, the interruption of natural relief continuity and the change of natural géomorphologie processes. The aim of this work, concerns the determination of the impacts to the environment and more specifically the geomorphes and geomorphological processes, by the bauxite ore exploitation and the quarrying activity, that was developed in the wider region of the "National Park of Iti".